(3EOGQI GdGSJKeGQ hGdeMGaX GdGSJKeGQjIs - (3eDjO YHO GdQMeGf(B, (3GdOhQjs ((3YeGf(B:s (3GKQGA(B,s, 2010)
(3eaghe GdGSJKeGQ h CgOGag , GdGShGb GdeGdjI h GdCOhGJ GdGSJKeGQjI , GdYGFO h GdeNGWQI , Jbjje GdSfOGJ h Jbjje GdCSge , TQcGJ GdGSJKeGQ , GdJfhjY h eNGWQ GdeMaXI , fehL JSYjQ GdCUhd GdQCSeGdjI , fXQjI JSYjQ GdeQGLMI , Jbjje COGA GdeMaXI h CNjQG GdeTJbGJ GdeGdjIs
Keywords: (3GdCShGb GdeGdjIs; (3GdESJKeGQs; (3GdESJKeGQ `` EOGQIs